2021
DOI: 10.1177/17085381211035291
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of allicin on vascular calcification via inhibiting endoplasmic reticulum stress

Abstract: Objectives Vascular calcification (VC) is an independent predictor for cardiovascular events and mortality. However, there are currently no effective methods to reverse or prevent it. The present study aimed to determine the ameliorative effect of allicin on VC. Methods VC model of rats was induced by high-dose vitamin D3, which was valued by Alizarin Red staining, calcium contents, and alkaline phosphatase in the aorta. Systolic blood pressure, pulse pressure, and pulse wave velocity were measured to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…We found that overexpression of DBP in CKD rats led to a reduction in the expression of RUNX2 and BMP2. Both RUNX2 and BMP2 serve as indicators of the osteoblastic phenotype in VSMCs and are often highly expressed in calcified aortas [ 27 ]. Therefore, the reduced levels of RUNX2 and BMP2 suggested a reduction in VC.…”
Section: Discussionmentioning
confidence: 99%
“…We found that overexpression of DBP in CKD rats led to a reduction in the expression of RUNX2 and BMP2. Both RUNX2 and BMP2 serve as indicators of the osteoblastic phenotype in VSMCs and are often highly expressed in calcified aortas [ 27 ]. Therefore, the reduced levels of RUNX2 and BMP2 suggested a reduction in VC.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, induced ATF4 expression due to increased stearate could contribute to enhanced osteoblastic differentiation as well as mineralization of VSMCs, involved with the activated PERK‐eIF2α pathway, thereby augmenting vascular calcification (Masuda et al 2012). Inhibition of PERK/eIF2α/ATF4 cascades due to Allicin treatment can attenuate aortic vascular calcification and stiffness (Wang et al 2022). Furthermore, inactivated PERK‐eIF2α‐ATF4 pathway due to pre‐culture of VSMCs using terpinen‐4‐ol or a SIRT1 agonist ameliorates vascular calcification (Zhang et al 2021a, b).…”
Section: Discussionmentioning
confidence: 99%
“…As all three branches of the UPR, the protein kinase-like ER kinase (PERK), inositol-requiring transmembrane kinase and endonuclease-1α (IRE1α), and activating transcription factor (ATF), are activated during bone formation to regulate expression of osteogenic genes, it is crucial to elucidate the role of endoplasmin in valve calcification [42][43][44][45][46]. Importantly, elevated levels of endoplasmin have been found in calcified vascular smooth muscle cells [47] and in the calcified aorta [48,49], consistent with our results.…”
Section: Discussionmentioning
confidence: 99%